A Case of Biliary Tract Infection Caused by KPC-2-Producing Kluyvera ascorbata. (11th April 2018) - Wang, Lu; Jing, Ying; Lai, Kaisheng; An, Jingna; Yang, Jiyong
Abstract : Kluyvera spp. can cause various infections. However, carbapenemase-producing Kluyvera spp. has not been previously reported. We report a case of biliary tract infection caused by KPC-2-producing K. ascorbata in a 13-year-old female. To the best of our knowledge, this is the first report on infection caused by carbapenemase-producing Kluyvera spp.